Method and Notation Application for Case Model Creation in the Social Sector - Lantow, Birger; Wichmann, Johannes; Herzog, Paul (Complex Systems Informatics and Modeling Quarterly, 2019)
Adaptive Case Management (ACM) is an approach for the management of knowledge-intensive processes. “Case Management Model and Notation” (CMMN) is an industry standard that can be used as a notation for process models in the context of ACM. However, CMMN only specifies a notation. Methods for process elicitation and management have not been well addressed by scientific investigations. This work assesses the method support and the feasibility of ACM on the example of a social care company. This company, on the one hand, represents a typical environment for ACM application and, on the other hand, contains some characteristics that are common for the social care industry. Thus, future development directions, a combined process and case approach for the social care company and an evaluation of existing and proposed methodology are provided in a qualitative way.